Catalytic, Stereoselective Dihalogenation of Alkenes: Challenges and Opportunities. Issue 52 (2nd December 2015) - Cresswell, Alexander J.; Eey, Stanley T.‐C.; Denmark, Scott E.
Abstract: Although recent years have witnessed significant advances in the development of catalytic, enantioselective halofunctionalizations of alkenes, the related dihalogenation of olefins to afford enantioenriched vicinal dihalide products remains comparatively underdeveloped. However, the growing number of complex natural products bearing halogen atoms at stereogenic centers has underscored this critical gap in the synthetic chemist's arsenal. This Review highlights the selectivity challenges inherent in the design of enantioselective dihalogenation processes, and formulates a mechanism‐based classification of alkene dihalogenations, including those that may circumvent the "classical" haliranium (or alkene‐dihalogen π‐complex) intermediates. A variety of metal and main group halide reagents that have been used for the dichlorination or dibromination of alkenes are discussed, and the proposed mechanisms of these transformations are critically evaluated. Abstract : One of the most vexing challenges in stereoselective synthesis is catalysis of alkene dihalogenation, under different activation modes, with control over both the absolute and relative stereochemical course of dihalogen addition. Dihalogenations that circumvent the "classical" haliranium intermediates provide new opportunities for catalysis, potentially having broader implications for the design of stereoselective alkene difunctionalizations.